Bridging the multimodal gap: from theory to practice - Khadka, Santosh, editor; Lee, J. C., editor; Utah State University Press, publisher (Colorado State University. Libraries, 2019)
Addresses multimodality scholarship and its use in the composition classroom and responds to the needs of instructors by exploring how multimodality can be implemented in courses and narrow the gap between those who engage in this instruction and those who are still exploring its pedagogical value.--Provided by publisher.
Introduction: extending the conversation / Santosh Khadka and J. C. Lee -- On multimodality / Rick Wyosocki, Jon Udelson, Caitlin E. Ray, Jessica S. B. Newman, Laura Sceniak Matravers, Ashanka Kumari, Layne M. P. Gordon, Khirsten L. Echols, Michelle Day, Michael Baumann, Sara P. Alvarez, and Dànielle Nicole DeVoss -- Re-imagining multimodality through UDL / Elizabeth Kleinfeld -- Dissipating hesitation / Jessie C. Borgman -- Reversing the process / Mark Pedretti and Adam Perzynski -- Thinking beyond multimodal projects / Tiffany Bourelle, Angela Clark-Oates, Andrew Bourelle, Matthew Irwin, and Breanne Potter -- Archiving digital journaling in first-year writing / Steven Alvarez -- Blogging multimodality / Kathleen Blake Yancey -- When multimodality gets messy / Jennifer J. Buckner -- Entering the multiverse / Rebecca Thorndike-Breeze, Aaron Block, and Kara Mae Brown -- Digital storytelling in the L2 graduate writing classroom / Joel Bloch -- Multimodality, transfer, and rhetorical awareness / Stephen Ferruci and Susan DeRosa -- Distributed assessment from the runway to the classroom / Areti Sakellaris -- Multimodal pedagogy & multimodal assessment / Shane A. Wood -- / In lieu of an afterword: rewriting the difference of multimodality / Bruce Horner.
Keywords: English language -- Rhetoric -- Study and teaching (Higher); Modality (Linguistics); Interdisciplinary approach in education